Research on aiming methods for small sample size shooting tests of two-dimensional trajectory correction fuse - Liang, C.; Shen, Q.; Deng, Z.; Li, H.; Pu, W.; Tian, L.; Lin, Z. (Defence Technology, 2024)
The longitudinal dispersion of the projectile in shooting tests of two-dimensional trajectory corrections fused with fixed canards is extremely large that it sometimes exceeds the correction ability of the correction fuse actuator. The impact point easily deviates from the target, and thus the correction result cannot be readily evaluated. However, the cost of shooting tests is considerably high to conduct many tests for data collection. To address this issue, this study proposes an aiming method for shooting tests based on small sample size. The proposed method uses the Bootstrap method to expand the test data; repeatedly iterates and corrects the position of the simulated theoretical impact points through an improved compatibility test method; and dynamically adjusts the weight of the prior distribution of simulation results based on Kullback-Leibler divergence, which to some extent avoids the real data being "submerged" by the simulation data and achieves the fusion Bayesian estimation of the dispersion center. The experimental results show that when the simulation accuracy is sufficiently high, the proposed method yields a smaller mean-square deviation in estimating the dispersion center and higher shooting accuracy than those of the three comparison methods, which is more conducive to reflecting the effect of the control algorithm and facilitating test personnel to iterate their proposed structures and algorithms.; in addition, this study provides a knowledge base for further comprehensive studies in the future.